Building Resilience to Disaster and Climate Change through Social Protection - World Bank (Washington, DC, 2014)
Natural disasters and climate change are among the greatest threats to development. Although natural disasters have always presented risks, climate change increases those risks and compounds them by adding a greater level of uncertainty. As a result of their increased frequency, the economic and social costs of disasters are mounting (World Bank 2010). Natural disasters and climate change can push people into chronic and transient poverty and force them to adopt negative coping strategies. Social protection programs play an important role in protecting poor and vulnerable people from these impacts and helping them reduce their exposure and vulnerability to them. This toolkit provides guidance on how to prepare social protection programs to respond to disasters and climate change. The snapshots of good practice experiences and practical tips for implementation are intended to guide decision makers in countries facing these risks in adapting their social protection programs to reduce negative impacts and accelerate recovery. The focus of this toolkit is aligned with the role and expertise of the World Bank, which has traditionally supported early and long-term recovery and helped rebuild livelihoods and infrastructure. This toolkit provides examples of good practice experiences and practical guidance for the practitioner in that direction.